Politicized microfinance money, power, and violence in the Black Americas - Hossein, Caroline Shenaz 1971- (University of Toronto Press, 2016)
When Grameen Bank was awarded the Nobel Peace Prize in 2006, microfinance was lauded as an important contributor to the economic development of the Global South. However, political scandals, mission-drift, and excessive commercialization have tarnished this example of responsible development. Politicized Microfinance insightfully discusses these negative developments while providing a path towards redemption. In this work, Caroline Shenaz Hossein explores the politics, histories and social prejudices that have shaped the legacy of microfinance in Grenada, Guyana, Haiti, Jamaica and Trinidad. Writing from a feminist perspective and via individual interviews, focus groups, historical analysis, ethnographic methods and participant observation, Hossein offers multiple solutions that prioritize the needs of marginalized and historically oppressed people of African descent. A must read for scholars of political economy, diasporas studies, women's studies, as well as development practitioners, Hossein deftly argues for microfinance to return to its origins as a political tool, fighting for those living in the margins.